2008
DOI: 10.1177/0363546507311093
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Tunnel Placement in Single-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: Current techniques to reconstruct the ACL focus on replacing the native 2-bundle ACL with a single-bundle graft.There is debate regarding the need to reconstruct both the posterolateral (PL) and anteromedial (AM) bundles of the ACL. The controversy has evolved out of the recognition that many surgeons inadvertently create a vertically oriented graft that may not adequately restore either the translational or rotational kinematic properties of an intact knee. A vertical femoral tunnel has been cited as 1 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 41 publications
2
30
0
2
Order By: Relevance
“…In an attempt to reduce the femoral tunnel obliquity using the transtibial technique, Rue et al21) moved the starting point of the tibial tunnel more proximally and medially than that in the conventional method and performed a 10- or 2-o’clock femoral tunnel placement. However, the limitations of their method included possible damage to the medial collateral ligament and pes anserinus, and difficulty to ensure firm fixation to the tibia due to the short tibial tunnel length.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to reduce the femoral tunnel obliquity using the transtibial technique, Rue et al21) moved the starting point of the tibial tunnel more proximally and medially than that in the conventional method and performed a 10- or 2-o’clock femoral tunnel placement. However, the limitations of their method included possible damage to the medial collateral ligament and pes anserinus, and difficulty to ensure firm fixation to the tibia due to the short tibial tunnel length.…”
Section: Discussionmentioning
confidence: 99%
“…This position was maintained for the same femoral tunnel location in all groups. The femoral aiming guide was rotated laterally so that the femoral tunnel could be placed more anatomically12,13). Finally, a 2.4-mm guide pin with a suture eyelet was inserted, and the femoral tunnel was drilled.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested modifications to the coronal plane alignment of the tibial tunnel in the transtibial technique for accurate femoral tunnel positioning and minimal errors4,6,1012). However, the literature is lacking on the effect of variation in the sagittal plane angle of the tibial tunnel in relation to the severity of tibial intra-articular aperture expansion caused by iatrogenic re-reaming in ACL reconstruction using the modified transtibial technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, two-dimensional anatomical scales, such as the “clock-face” reference and quadrant method, were developed as a fixed and universal scaling method to describe the anatomical location of the ACL insertion site and graft placement. The “clock-face” reference has been utilized for referring the coronal position of the ACL insertion site and graft placement [2729]. This reference system is able to be adopted for arthroscopic images [30].…”
Section: Progression Of the Imaging Technology For The Acl Anatomymentioning
confidence: 99%